Towards reproducible research in recurrent pregnancy loss immunology: Learning from cancer microenvironment deconvolution - Betti, Martina; Vizza, Enrico; Piccione, Emilio; Pietropolli, Adalgisa; Chiofalo, Benito; Pallocca, Matteo; Bruno, Valentina (Frontiers in Immunology, 2023)
The most recent international guidelines regarding recurrent pregnancy loss (RPL) exclude most of the immunological tests as recommended for RPL, since they do not reach an evidence-based level. Comparisons for metanalysis and systematic reviews are limited by the ambiguity in terms of RPL definition, etiological and risk factors, diagnostic work-up and treatments applied. Therefore, cohort heterogeneity, inadequacy of numerosity and quality of data confirm a not standardized research quality in RPL field, especially for immunological background, for which potential research application remains confined in a separate single biological layer. Innovative sequency technologies and databases have proved to play a significant role in the exploration and validation in Cancer Research in terms of datasets quality and bioinformatics tools. In this article we will investigate how bioinformatics tools born for large-scale cancer immunological research could revolutionize RPL immunological research but are limited by the nature of current RPL datasets.